2009
DOI: 10.1007/s00221-009-1883-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of visual feedback alters muscle activity and reduces force variability during constant isometric contractions

Abstract: The purpose of this study was to compare force accuracy, force variability and muscle activity during constant isometric contractions at different force levels with and without visual feedback and at different feedback gains. In experiment 1, subjects were instructed to accurately match the target force at 2, 15, 30, 50, and 70% of their maximal isometric force with abduction of the index finger and maintain their force even in the absence of visual feedback. Each trial lasted 22 s and visual feedback was remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
97
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 40 publications
14
97
2
2
Order By: Relevance
“…When comparing our findings with those during visual feedback removal present in the literature (Vaillancourt and Russell 2002;Baweja et al 2009;Prodoehl and Vaillancourt 2010;Tracy 2007b), somehow similar data can be found showing a force drift from the force target when visual feedback was taken away, especially at high force levels. This phenomenon became more evident as force level increased (Baweja et al 2009).…”
Section: Effect Of Visual Feedback (Nofb-1 Vs Fb )supporting
confidence: 88%
See 4 more Smart Citations
“…When comparing our findings with those during visual feedback removal present in the literature (Vaillancourt and Russell 2002;Baweja et al 2009;Prodoehl and Vaillancourt 2010;Tracy 2007b), somehow similar data can be found showing a force drift from the force target when visual feedback was taken away, especially at high force levels. This phenomenon became more evident as force level increased (Baweja et al 2009).…”
Section: Effect Of Visual Feedback (Nofb-1 Vs Fb )supporting
confidence: 88%
“…The amplitude of force fluctuation, an index of force stability, is also inversely related to the level of effort and to the number of the recruited motor units (Hamilton et al 2004), and has been shown to be influenced directly by alterations in synergistic muscle activation (Shinohara et al 2009). Overall, visual feedback removal during an isometric task either did not influence (Christou et al 2004;Vaillancourt and Russell 2002) or reduce force variability /accuracy making more stable the signal Christou 2005;Tracy et al 2007;Baweja et al 2009;Kennedy and Christou 2011;Schiffman et al 2002;Tracy 2007b). Conversely, Moreover, when visual feedback is removed, the force accuracy was compromised because the force output tended to drift away from the required target (Tracy 2007b;Vaillancourt and Russell 2002).…”
Section: Donementioning
confidence: 93%
See 3 more Smart Citations